Evolution of gene expression after whole‐genome duplication: New insights from the spotted gar genome. Issue 7 (25th September 2017) - Pasquier, Jeremy; Braasch, Ingo; Batzel, Peter; Cabau, Cedric; Montfort, Jérome; Nguyen, Thaovi; Jouanno, Elodie; Berthelot, Camille; Klopp, Christophe; Journot, Laurent; Postlethwait, John H.; Guiguen, Yann; et al.
Abstract: Whole‐genome duplications (WGDs) are important evolutionary events. Our understanding of underlying mechanisms, including the evolution of duplicated genes after WGD, however, remains incomplete. Teleost fish experienced a common WGD (teleost‐specific genome duplication, or TGD) followed by a dramatic adaptive radiation leading to more than half of all vertebrate species. The analysis of gene expression patterns following TGD at the genome level has been limited by the lack of suitable genomic resources. The recent concomitant release of the genome sequence of spotted gar (a representative of holosteans, the closest‐related lineage of teleosts that lacks the TGD) and the tissue‐specific gene expression repertoires of over 20 holostean and teleostean fish species, including spotted gar, zebrafish, and medaka (the PhyloFish project), offers a unique opportunity to study the evolution of gene expression following TGD in teleosts. We show that most TGD duplicates gained their current status (loss of one duplicate gene or retention of both duplicates) relatively rapidly after TGD (i.e., prior to the divergence of medaka and zebrafish lineages). The loss of one duplicate is the most common fate after TGD with a probability of approximately 80%. In addition, the fate of duplicate genes after TGD, including subfunctionalization, neofunctionalization, or retention of two "similar" copies occurred not only before but also after the divergence of species tested, in consistency with a role of the TGD in speciation and/or evolution of gene function. Finally, we report novel cases of TGD ohnolog subfunctionalization and neofunctionalization that further illustrate the importance of these processes. GRAPHICAL ABSTRACT: After the teleost‐specific genome duplication (TGD), the loss of one of the duplicate genes is the most common fate with a probability of 80%. After TGD, subfunctionalization, neofunctionalization, or retention of two 'almost similar' copies occur not only before, but also after the radiation of species tested.